Về các phép mã hóa hợp lý - Nghĩa, Huỳnh Hữu (Journal of Computer Science and Cybernetics, 2016)
In process to implement a database scheme with “good” qualities, at the first step, we often assign to each of the set of entities a number (a code). Making note that almost the complexity of conceptual algorithms is usually, at least, proportional to number of codes of  attributes, and to the length of the dependency set, we study methods are so-called “logical codings”. In this paper, we study logical codings on an universal U =<S,F>, in which S is the set of attributes, F is the set of functional dependencies. Those logical codings are to be proven independent to all conceptual algorithms. And at the final, we introduce the  logical codings NGH which has low complexity and produces a minimal set of codes.